Understanding of Tobacco and Lung Cancer Among Medical Students in Kathmandu University School of Medical Sciences (KUSMS) - Khatiwada, Prashant; Kayastha, SR; Pant, P; Khanal, KR; Giri, A; Khatiwoda, P; Mali, A (Kathmandu University Medical Journal, 2013)
Background Often, lung cancer is diagnosed at terminal stages. Poor awareness about the symptoms or risk factors of lung cancer among medics may be one of the factors for delayed diagnosis. Objective We explored the knowledge of medical students and their behavior with the patients of lung cancer. Method Qualitative and quantitative approaches were used for data collection from 153 medical student of Kathmandu University School of Medical Sciences from December 2011 to May 2012. Results Among the results, eighty-nine students had over 80% knowledge of the 14 cancer warning signs, among them 83% knew the nine risk factors for lung cancer. Twenty-three students told lung cancer can be hereditary. Sixty five percent of all participants believed that lung cancer can be detected at early stage; of them 81% told that it can be treated. About 24% of the total students were current or ex-smokers and about half of them believed that lung cancer does not occur in light smokers. Only 10% have heard of Framework Convention on Tobacco Control in Nepal. Conclusion Study finds that all medical students who know about any cancers may not necessarily have knowledge about lung cancers. Their perception about the cause of lung cancer may be influenced by their smoking behavior and there was little knowledge of public health measures for smoking control. Awareness about national policies needs to be increased. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 60-65 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8022